DEVELOPMENT OF LEARNING DEVICES BASED ON ETHNOMATHEMATICS OF THE MEHER TRIBE WOVEN FABRICS (KISAR ISLAND) WITH REALISTIC MATHEMATICS EDUCATION APPROACH ON NUMBER PATTERN MATERIAL - Dahoklory, Andy Sunder Keer; Laurens, Theresia; Palinussa, Anderson L (Jurnal Pendidikan Matematika (JUPITEK), 2023)
This study aimed to develop a learning device based on ethnomathematics of the Meher tribe woven fabrics (Kisar Island) with a Realistic Mathematics Education (RME) approach on number pattern material for 8th-grade students of Public Junior High School 4 Southern Islands. The learning devices developed consisted of Learning Implementation Plans (RPP), Teaching Materials (BA), and Student Worksheets (LKPD). The development model used was the 4-D model, which consisted of four stages, namely define, design, develop, and disseminate but were limited to the development stage. The device was tested for quality (valid, practical and effective). Following the validation results by the five validators, it was found that the devices developed met the validity requirements with an average score of Learning Implementation Plans (RPP) 3.5 (very good), an average score of Teaching Materials (BA) 3.3 (good), the average score of Student Worksheets (LKPD) was 3.4 (good). The average validator's general assessment was 3.3 (good). According to the practicality test of the developed devices, it was found that the developed devices were categorized as practical, with an average positive response of educators of 100% and an average positive response of students of 91.3%. The developed devices also fulfilled the effectiveness requirements by achieving a classical completeness percentage of 79.2%. The results of the study obtained the quality of the devices developed